THE INFLUENCE OF TECHNOLOGICAL PARAMETERS OF MILLING ON THE GEOMETRIC DIMENSIONS OF PRINTED CIRCUIT BOARDS - Невлюдов, Игорь; Никитин, Дмитрий; Мижирицкий, Вадим (SWorldJournal, 2021)
The materials of the work present the results of the study of the influence of technological parameters of milling on the preservation of the geometric dimensions of printed circuit boards (PBC), the quality of the surface after processing. For the study,